2021
DOI: 10.1145/3494960
|View full text |Cite
|
Sign up to set email alerts
|

Are Those Steps Worth Your Privacy?

Abstract: Fitness trackers are increasingly popular. The data they collect provides substantial benefits to their users, but it also creates privacy risks. In this work, we investigate how fitness-tracker users perceive the utility of the features they provide and the associated privacy-inference risks. We conduct a longitudinal study composed of a four-month period of fitness-tracker use (N = 227), followed by an online survey (N = 227) and interviews (N = 19). We assess the users' knowledge of concrete privacy threats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(2 citation statements)
references
References 81 publications
0
1
0
Order By: Relevance
“…We also explore more detailed perceptions regarding notification preferences and how occupants want to be informed of data collection. Via in situ studies, some previous work found users' privacy concerns or misunderstanding of the facial recognition technology [48], [49] and fitness tracker [42]. In particular, Zhang et al [48], [49] studied people's notification preferences, including the frequency of notifications.…”
Section: Iot Privacymentioning
confidence: 99%
“…We also explore more detailed perceptions regarding notification preferences and how occupants want to be informed of data collection. Via in situ studies, some previous work found users' privacy concerns or misunderstanding of the facial recognition technology [48], [49] and fitness tracker [42]. In particular, Zhang et al [48], [49] studied people's notification preferences, including the frequency of notifications.…”
Section: Iot Privacymentioning
confidence: 99%
“…However, dark patterns [16] and common usability errors such as non-privacy-related labels often make privacy settings even more difcult to fnd, and understand [18], or users are unaware of the related security risks [24], underlying today's user challenges to control their data [4]. This issue is further exacerbated by ftness tracker users forgetting their privacy settings or having inaccurate mental models of corresponding processes [48] and how ftness tracker ecosystems work [43]. A large body of research has been dedicated to addressing these limitations and increasing the digital sovereignty and self-determination of the individual.…”
Section: Introductionmentioning
confidence: 99%